Sodium alendronate: proposal and reliability of indicators (Brazilian Journal of Pharmaceutical Sciences, 2022)
The present study proposes and evaluates the test-retest reliability of indicators of the correct use of sodium alendronate in elderly patients. This is a test-retest reliability study for use of sodium alendronate. Six questions to evaluate the correct use of this medicine were elaborated after analysis of information in the literature. Data collection was performed through questionnaires in face-to-face in-home interviews by previously trained interviewers. The participants were initially interviewed (test) when they agreed to participate in the study, and secondly (retest), after a period of 7 to 14 days from the first interview. The reliability of the questions was evaluated by means of the agreement percentage and the Kappa coefficient. Fifty-seven pairs (test-retest) were obtained. The mean age was 69.3 (SD = 6.9) years, the majority (92.5%) completed elementary education, and declared themselves white (50.9%). All the questions presented high concordance ranging from 79.0% to 98.3%. The Kappa values ranged from 0.1 (low) to 0.83 (very good). The agreement percentage and the Kappa values suggest adequate reliability of the proposed questions. We suggest that they can be used as a simple and quick way to evaluate the quality of sodium alendronate use among the elderly.